2015
DOI: 10.1037/pspp0000051
|View full text |Cite
|
Sign up to set email alerts
|

Why do the lonely stay lonely? Chronically lonely adolescents’ attributions and emotions in situations of social inclusion and exclusion.

Abstract: The goal of this study was to identify mechanisms associated with chronic loneliness by examining the effect of adolescents' accumulated history of loneliness on responses to new social situations. Specifically, this study investigated whether attributions and emotions in situations of social inclusion and exclusion differ between chronically lonely adolescents and adolescents with a different loneliness history. A total of 730 adolescents (Mage at Wave 1 = 15.43 years) participated in a 4-wave longitudinal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(97 citation statements)
references
References 88 publications
3
90
2
2
Order By: Relevance
“…Negative self-cognitions are found in children that have low peer support; those that have experienced peer victimisation (Sinclair et al 2012), or report to be lonely (Vanhalst et al 2015). Negative self-cognitions colour individuals' appraisal and behaviour in interpersonal situations and negatively influence individuals' memories of these situations (Beck, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Negative self-cognitions are found in children that have low peer support; those that have experienced peer victimisation (Sinclair et al 2012), or report to be lonely (Vanhalst et al 2015). Negative self-cognitions colour individuals' appraisal and behaviour in interpersonal situations and negatively influence individuals' memories of these situations (Beck, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Information about the duration of loneliness or multiple assessments over a longer period are needed to examine whether the association with state loneliness differs depending on how long trait loneliness has persisted, as the duration of loneliness may affect daily life experiences. For example, Vanhalst et al (2015) found evidence for hypervigilance to social exclusion and hypovigilance to social inclusion only in adolescents who experienced loneliness throughout adolescence, which could indicate that this group may encounter particularly negative social experiences in daily life as well. Further research should measure the duration of trait loneliness in order to examine whether the duration of loneliness affects daily life experiences.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In line with this idea, earlier research showed loneliness was related to having a hostile attribution bias (Qualter et al 2013), and to a self-defeating attribution style in which social success is attributed to external factors and social failure to internal factors (Crick and Ladd 1993). In addition, chronic loneliness is related to the tendency to attribute social exclusion to internal and stable factors, and social inclusion to unstable and external factors (Vanhalst et al 2015). Moreover, there is evidence to suggest that lonely adolescents may view the quality of their friendships more negatively than their friends do (Lodder et al 2015), and that they show greater negative affect tin response to negative company (van Roekel et al 2014).…”
Section: Introductionmentioning
confidence: 99%